(untitled) (International Journal of Food and Nutritional Sciences, 2022)
New Pension Scheme is launched in 2004 to provide a retirement financial safety to employees. Afterwards it has been expanded from government employees to private sector employees. Currently it is available to any person who aims at invest in this scheme voluntarily. Mutual fund has been considered as a most flexible and versatile investment alternative across all categories of investors.